Alchemy in the Vernacular: An Edition and Study of Early English Witnesses of The Mirror of Alchemy - Norja Sara (Modern Language Society in Helsinki, 2022)
The author defended her doctoral dissertation Alchemy in the Vernacular: An Edition and Study of Early English Witnesses of The Mirror of Alchemy at the University of Turku, Faculty of Humanities, on 27 May 2021. Professor Peter J. Grund (University of Kansas) acted as the opponent and Professor Matti Peikola (University of Turku) acted as the Custos. The dissertation is available at https://www.utupub.fi/handle/10024/151694